Densitas Simbion Alga Zooxanthellae pada Anemon Laut Stichodactyla gigantea Alam dan Hasil Reproduksi Aseksual - Tuwo, Ambo; Budimawan, Budimawan; Niartiningsih, Andi; Rifa’i, M. Ahsin (Jurnal Natur Indonesia, 2013)
The aims of this research were to discover the density of algae symbiont of zooxanthellae in the giant carpet anemone (Stichodactyla gigantea) from the nature and the asexual reproduction by longitudinal body fragmentation technique. The research was conducted from October 2007 to July 2008, in The Hatchery of University of Hasanuddin Marine Station in Barrang Lompo Island for seed production and coral reefs area of Barrang Lompo Island for the implementation of culture. The series of study was started with parental collection and acclimatization of anemones, fragmentation of the body, culturing anemones in the coral reefs area and collection of algae zooxanthellae which is conducted every two months. The results of this study indicated the difference of zooxanthellae density from nature and asexual reproduction anemones. The highest density of zooxanthellae algae found in the non fragmented or nature population (AA) (10.84 x 106 cell/cm2), followed by the anemone which was resulted from 2 parts body fragmentation (AF2) (10.24 x 106 cells/cm2), and the anemone which was resulted from 4 parts body fragmentation (AF4) (9.17 x 106 cell/cm2 ). Whereas, between the good coral (KB) and bad coral (KR) not significant.